2023
DOI: 10.3390/agronomy13102549
|View full text |Cite
|
Sign up to set email alerts
|

AMMI Analysis of Genotype × Environment Interaction on Sugar Beet (Beta vulgaris L.) Yield, Sugar Content and Production in Romania

Camelia Oroian,
Florin Ugruțan,
Iulia Cristina Mureșan
et al.

Abstract: The overall yield and sugar content of sugar beet (Beta vulgaris L.) were determined by the genotype and its interaction with the environment. This study aimed to analyze the interaction of 23 genotypes with different environmental conditions during two growing seasons. To estimate the variance of genotypes, environment, and genotype function of the environment, the R 3.5.1 software package was used. In addition, the multivariate stability method was used to explain the G (genotype) × E (environment) interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…According to Oroian et al [ 34 ], the highly significant effect of the linear part of the GEI indicated few similarities among the genotypes in the studied environments. They also point out that selecting well-adapted genotypes is more difficult due to the effects of the GEI on genotype performance.…”
Section: Discussionmentioning
confidence: 97%
“…According to Oroian et al [ 34 ], the highly significant effect of the linear part of the GEI indicated few similarities among the genotypes in the studied environments. They also point out that selecting well-adapted genotypes is more difficult due to the effects of the GEI on genotype performance.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, G1 shows a better yield and stability in the GGE biplot but a better yield and worse stability in the AMMI model. The slight difference between the two methods may be related to the fact that GGE considered GEI in addition to G [39,41].…”
Section: Yield and Stability Of 11 Maize Hybrid Varietiesmentioning
confidence: 99%